Peran Mediasi dalam Penyelesaian Sengketa Sertipikat Gandadi Badan Pertanahan Nasional (BPN) Kabupaten Klungkung - I Gede Agus Marta Dinata; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Land or territory is the main element of a country. The magnitude of the influence of land on human life, makes the State obliged to guarantee legal certainty for the land rights even though these rights are still limited by the interests of other people, society, and the state. From the background, problems can be formulated such as 1). How is the dual certificate dispute resolution through mediation at the Klungkung Regency National Land Agency (BPN)? 2). What are the obstacles in resolving a double certificate dispute at the National Land Agency (BPN) Klungkung Regency? This research is empirical legal research by describing the law as law in action. The state policy on land tenure security was strengthened and its rights and obligations were regulated in the Basic Agrarian Law (UUPA) issued in 1960. Nevertheless, land issues cannot be spared from people's lives. One of the problems that often occurs is the existence of multiple certificates. In this case, the National Land Agency has an important role to play in resolving it.